Microstructure, tensile and impact behaviour of Si3N4 particles reinforced Al2024 matrix composites. (2022) - Dharshan, K.; Raju, T.N.; Nagaral, Madeva; Bharath, V.; Auradi, V.; Shantharaj, P.; Supreeth, S.
Abstract: Aluminium MMC's are used in wide range of applications because of its strength to weight ratio and enhanced mechanical properties due to addition of reinforcement. Different types of reinforcement helped in enhancement of mechanical properties either a hybrid or single reinforcement. In this work we carried out reinforcement of Si3 N4 with Al2024 alloy. Aluminium 2000 series has good toughness, ductility and fatigue resistance compared to other series. Liquid metallurgy technique process is adopted and stir casting process is carried out to prepare Al2024-Si3 N4 composite. 4 and 8 wt% composition of Si3 N4 in aluminium alloy. Tensile and impact test are conducted to know the elastic property and toughness of the material. Yield strength, tensile strength and elongation percentage is increased till 4 wt% of Al2024-Si3 N4 and decreased for 8 wt% of Al2024-Si3 N4 . The Impact resulted showed the same, increase for 4% and decrease for 8%. Microstructural analysis is done with the help of scanning electron microscope to know the distribution of Si3 N4 in Al2024 alloy.